Zathura - Jon, Favreau; Koepp, David; Kamps, John.; Sony Pictures Home Entertainment (Firm).; Columbia Pictures; Radar Pictures/Teitler Film/Michael De Luca production; Magna Vision ([Culver City, Calif.] Sony Pictures Home Entertainment ; distributed in the Philippines by MagnaVision, 2005)
Danny twists the key of an old science fiction game. The game unleashes a localized meteor shower and wrenches Danny's house into orbit around a distant ringed planet. Besides Danny, his brother Walter and sister Lisa have to go along. Soon a defective robot, a rangy astronaut, and an alien spaceship enter the picture. The only way the kids can return their house to its proper space-time coordinates is to finish the game, but before they can finish, the game board falls into the hands of some rather nasty, carnivorous lizards.
Based on the book by Chris Van Allsburg.
Director of photography, Guillermo Navarro ; art directors, David F. Klassen, Richard F. Mays ; editor, Dan Lebental ; music, John Debney ; costume designer, Laura Jean Shannon ; production designer, J. Michael Riva ; visual effects supervisors, Joe Bauer, Peter G. Travers.
Jonah Bobo, Josh Hutcherson, Dax Shepard, Kristen Stewart, Tim Robbins, John Alexander.
MPAA rating: PG; fantasy action and peril, and some language.
VCD.
Keywords: Board games -- Drama; Orbital transfer (Space flight) -- Drama; Brothers and sisters -- United States -- Drama